Transition between grain boundary and intragrain scattering transport mechanisms in boron-doped zinc oxide thin films - Steinhauser, Jérôme; Fay, Sylvie; Oliveira Nascimento, Nuno; Vallat-Sauvain, Evelyne; Ballif, Christophe (My University, 2007)
A comprehensive model for the electronic transport in polycrystalline ZnO:B thin films grown by low pressure chemical vapor deposition is presented. The optical mobilities and carrier concentration calculated from reflectance spectra using the Drude model were compared with the data obtained by Hall measurements. By analyzing the results for samples with large variation of grain size and doping level, the respective influences on the transport of potential barriers at grain boundaries and intragrain scattering could be separated unambiguously. A continuous transition from grain boundary scattering to intragrain scattering is observed for doping level increasing from 3×1019 to 2×1020 cm−3.